Research on channel-fixed delay error estimation of wideband digital array radar - Xiaobei ZHANG; Quan ZHANG; Ming FANG; Kun QIN; Qi ZHANG (Tongxin xuebao)
A channel-fixed delay error estimation method was proposed to tackle the performance degradation of digital beamforming caused by the channel-fixed delay error of wideband digital array radar.First, the integer part of the fixed delay of the channel was estimated through the correlation integral peak of the baseband transmitted signal and the baseband received signal containing unknown delay parameters.Then, the fractional part of the fixed delay of the channel was estimated with parabolic interpolation by using the correlation peak and its adjacent two points.Finally, the multi-channel fixed delay error was calculated and compensated.The simulation results show that the multi-channel fixed delay estimation of wideband digital array radar can be realized on Xilinx xcku115.The estimative precision can reach 0.001～0.014 times the sampling gap when the signal-to-noise ratio of the input signal is 10～30 dB.The proposed method can meet the engineering application requirements and improve the performance of digital beamforming in wideband digital array radar.